A highly selective electrochemical sensor for nifedipine based on layer‐by‐layer assembly films from polyaniline and multiwalled carbon nanotube. Issue 21 (9th February 2016) - Wang, Qiguan; Zhao, Rongna; Wang, Sumin; Guo, Hao; Li, Jinhua; Zhou, Hongwei; Wang, Xinhai; Wu, Xinming; Wang, Yan; Chen, Weixing; Zhang, Wenzhi
ABSTRACT: An uniformly distributed film consisting of polyaniline (PANI) nanoparticles and carboxylic acid functionalized multiwalled carbon nanotubes (MWNTs‐COOH) was successfully assembled on ITO plates from a layer‐by‐layer (LBL) method by using electrostatic interactions as the main driving force. The good conjugation between PANI nanoparticles and MWNTs‐COOH resulted in significant electrochemical performance variation of the obtained films. In addition, the assembled MWNT‐COOH/PANI/ITO showed synergistic effect to the electrochemical oxidation of nifedipine (NIF) when used as a sensor. Compared with bare ITO, the oxidation potential of NIF can be decreased about 170 mV on MWNT‐COOH/PANI/ITO, and the lower detection limit of NIF was as low as 1.0 × 10 −6 mol/L. In addition, the assembled electrode gave no responses to interferences such as glucose, urea, ascorbic acid, and trisodium citrate, which showed high selectivity for recognition and quantification of NIF. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 43452. Abstract :